Interpretasi Makna Lirik Lagu “Ada Titik-Titik di Ujung Doa” Karya Sal Priadi melalui Pendekatan Hermeneutik Schleiermacher - Lilipory, Anna Novinta; Soplanit, Felani; Anakotta, Elka (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study seeks to interpret the meaning of the lyrics in the song “Ada Titik‑Titik di Ujung Doa” by Sal Priadi through Schleiermacher’s hermeneutic approach. The song reveals a subtle spiritual dimension by means of metaphor and poetic language, portraying prayer as a personal, reflective, and hope‑laden form of inner conversation amid the uncertainty of life in the post‑pandemic era. By adopting a qualitative interpretive method, the research examines the song lyrics through Schleiermacher’s two principal dimensions: grammatical interpretation and psychological interpretation. The analysis shows that prayer in this song is not merely a conventional religious ritual, but an existential expression of human beings facing loss, isolation, and unfulfilled hopes. The phrase “titik‑titik di ujung doa” functions as a symbolic space of incomplete psycho‑spiritual longing, in which prayer is understood as an open, fragmented, and repetitive process, as well as a medium for reconciling with the past and seeking forgiveness for both oneself and others. Within Schleiermacher’s hermeneutic framework, the interpretation of these lyrics suggests that prayer in contemporary Indonesian pop music serves as a representation of human resilience, personal, reflective, and subtly critical of the notion that divine response must always be complete and perfectly resolved.